Impact of CO2 concentration and ambient conditions on microalgal growth and nutrient removal from wastewater by a photobioreactor - Al Momani, F.; Alketife, A.; Judd, S.; Bhosale, R.; Shurair, M.; Znad, Hussein; Tawalbeh, M. (Elsevier, 2019)
The increase in atmospheric CO2concentration and the release of nutrients from wastewater treatment plants(WWTPs) are environmental issues linked to several impacts on ecosystems. Numerous technologies havebeen employed to resolves these issues, nonetheless, the cost and sustainability are still a concern. Recently,the use of microalgae appears as a cost-effective and sustainable solution because they can effectively uptakeCO2and nutrients resulting in biomass production that can be processed into valuable products. In this study sin-gle (Spirulina platensis(SP.PL)andmixed indigenous microalgae(MIMA) strains were employed, over a 20-monthperiod, for simultaneousremoval of CO2fromflue gases and nutrientfrom wastewater under ambient conditionsof solar irradiation and temperature. The study was performed at a pilot scale photo-bioreactor and the effect offeed CO2gas concentration in the range (2.5–20%) on microalgae growth and biomass production, carbon diox-ide bio-fixation rate, and the removal of nutrients and organic matters from wastewater was assessed. TheMIMAculture performed significantly better than the monoculture, especially with respect to growth and CO2bio-fixation, during the mild season; against this, the performance was comparable during the hot season. Optimumperformance was observed at 10% CO2feed gas concentration, thoughMIMAwas more temperature and CO2concentration sensitive.MIMAalso provided greater removal of COD and nutrients (~83% andN99%) thanSP.PLunder all conditions studied. The high biomass productivities and carbon bio-fixation rates(0.796–0.950 gdw·L-1·d-1and 0.542–1.075 gC·L-1·d-1contribute to the economic sustainability of microalgae as CO2removal process. Consideration of operational energy revealed that there is a significant energy benefitfrom cooling to sustain the highest productivities on the basis of operating energy alone, particularly if the indig-enous culture is used.